Bacterial Colonization of the Hospitalized Newborn: Competition Between Staphylococcus aureus and Staphylococcus epidermidis. Issue 7 (July 2019) - Lee, Daniel C.; Kananurak, Anchasa; Tran, Michelle TN; Connolly, Patricia A.; Polage, Christopher R.; Iwase, Tadayuki; Bevins, Charles L.; Underwood, Mark A.
Abstract : Background: In adults, Staphylococcus epidermidis and Staphylococcus aureus compete for colonization of the nasal mucosa and S. epidermidis strains that produce the Esp serine protease eradicate S. aureus nasal colonization. Whether similar phenomena are seen in newborn infants is unknown. Methods: Nasal swabs were obtained on admission and discharge from newborn infants (n = 90 and 83, respectively) in the neonatal intensive care unit at UC Davis Children's Hospital. Swabs were cultured for S. aureus and S. epidermidis . S. epidermidis isolates were tested for Esp expression, overall secreted protease activity and biofilm inhibition. Results: No infant had S. aureus on admission. S. epidermidis colonization was rare on admission in inborn infants (2.5%), but common in infants transferred from referring hospitals (50%). At discharge, most infants (96%) were colonized by staphylococci. S. aureus colonization was less common in infants with S. epidermidis colonization (9%) and more common in infants without S. epidermidis (77%) (relative risk of S. aureus colonization in infants colonized with S. epidermidis 0.18, 95% confidence interval: 0.089–0.34, P < 0.0001). Compared with S. epidermidis strains from infants without S. aureus, S. epidermidis from infants co-colonized with S. aureus had lower total proteolytic enzyme activity and decreased biofilm inhibition capacity, but did not have lower frequency of Esp positivity. Conclusions: In hospitalized neonates, S. epidermidis colonization has a protective effect against S. aureus colonization. Secretion of proteases by S. epidermidis is a possible mechanism of inhibition of S. aureus colonization; however, in this cohort of neonates, the source of major protease activity is likely other than Esp. Abstract : Supplemental Digital Content is available in the text.